Should Patient with Autoimmune Inflammatory Rheumatic Diseases (AIIRD) be vaccinated with COVID-19 Vaccines? - Cesarius Singgih Wahono; Perdana Aditya; Faisal Parlindungan; RM. Suryo Anggoro KW; Anna Ariane; Herlina Yani; Andi Raga Ginting; Lisa Kurnia Sari; Pande Ketut Kurniari; Ratih Manuaba; Ika Vemilia; Rudy Hidayat; Sumariyono Sarmidi; Harry Isbagjo (Indonesian Rheumatology Association, 2021)
Vaccination is a very important measure for the prevention of various infections worldwide including the recent COVID-19 disease. However, until now the COVID-19 vaccine with various platforms has not been clinically tested on autoimmune inflammatory rheumatic disease (AIIRD) patients, due to caution against possible side effects and unknown efficacy. Several recent studies proved that there is increased risk of SARS-CoV-2 infection in AIIRD patients and moreover, those patients also have worse COVID-19 outcomes. Thus, patients with AIIRD should be prioritized for vaccination because they have an increased burden of infections, including COVID-19. Many studies showed that inactivated/non-live vaccine is safe for AIIRD patients and do not cause disease exacerbations. We conclude that benefits of vaccination greatly outweigh the risks of infection and therefore, COVID-19 vaccines can also be administered safely in stable AIIRD patients.